The ADDIE Analysis Phase in Arabic Module Design for Ugandan Adult Muallaf (UAM) Implications for the Development of Elementary Arabic Learning Modules (EALM) - Kirembwe Rashid Abdul Hamed; Mohd Aderi bin Che Noh; Siti Rosilawati binti Ramlan; Sakinah binti Ahmad; Hayati binti Ismail; Sarifah Nurhanum binti Syed Sahuri; Hishomudin Ahmad; Noor Azizi Ismail; Adibah binti Sulaiman @ Mohamad; Mardhiah Binti Yahaya; Mohammad Najib Jaffar (Penerbit USIM, 2024)
This research investigatedArabicneeds for Ugandan -adults muallafUAMusing the first phase of ADDIE; (analyze, design, develop, implement, and evaluate)in favor of developing the elementary Arabic learning module EALM for UAM. This research marked theStep (One)out of ADDIE (Five) steps of academic module development. It was meant to explore Arabic learning needs for UAM in order toidentify the major aspects forthe proposed EALM development. The study used a descriptive method with purposive UAM sample sized (n=40). The valid and reliable quesstionnaire of 5 Likert scales was used and the total reliability coefficient of which was ( r )=.984 for 128 items. The major results showed that UAM needed Arabic language for nine basicpurposes including religious, social, communication, education, business, self satisfaction, diplomatic, security and legal purposes. The general implication of findings confirmed that UAM Arabic weakness was a reflection of weaknesses in their Arabic curriculum. The researchers recommended to consider thise finding in the processof building EALM for UAM with samples of lessons using elementary Arabic grammarEAG,morphology and common arabic vocabularies CAV.